1998
DOI: 10.1088/0268-1242/13/3/004
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent calculation of facet heating in asymmetrically coated edge emitting diode lasers

Abstract: A numerical model is introduced that self-consistently calculates the time dependent axial variations of photon density, carrier density and temperature in semiconductor lasers. The most important approximations are outlined. In order to illustrate the capability of the model, some results are shown for an asymmetrically coated DQW GaAs/GaAlAs edge emitting laser diode. The temperature rise at the facets and the corresponding profiles of carrier and photon density are calculated. The asymmetric behaviour of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Consequently, the shape of the thermal profile REVIEW ARTICLE 429 along the laser axis defines the requirements to be fulfilled by the method. Menzel [106] calculated a more than 20 percent ΔT -reduction after 1 μm along the laser axis, while Eliseev [9] and Chen et al [12] found values even in the sub-μm range. Epperlein et al determined a 1/e T -decaylength from the front facet temperature along the laser axis of 6 μm by analysis of electroluminescence spectra [39].…”
Section: Facet Temperature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the shape of the thermal profile REVIEW ARTICLE 429 along the laser axis defines the requirements to be fulfilled by the method. Menzel [106] calculated a more than 20 percent ΔT -reduction after 1 μm along the laser axis, while Eliseev [9] and Chen et al [12] found values even in the sub-μm range. Epperlein et al determined a 1/e T -decaylength from the front facet temperature along the laser axis of 6 μm by analysis of electroluminescence spectra [39].…”
Section: Facet Temperature Analysismentioning
confidence: 99%
“…For devices with the lowest surface recombination velocities, the asymmetry of the carrier profile (caused originally by the asymmetric coating) is enhanced and the bulk temperature close to the rear facet notably increases compared to the front section. This is caused by Auger recombination [106]. Although the thermal runaway remains the trigger of the COD, the Auger heating of the bulk close to the rear facet substantially contributes to the total rear facet temperature and thus promotes COD there.…”
Section: Review Articlementioning
confidence: 99%
“…First, there is the z-profile of the nonequilibrium carrier density in the QW. In an operating laser, this concentration increases towards the rear, while the opposite holds for the photon density [12]. Since we monitor the nonequilibrium carrier density, an increasing SWIR signal towards the rear becomes plausible.…”
Section: A Cw Operationmentioning
confidence: 94%
“…For I=14.5 A we estimate =1.6, corresponding to a local temperature rise 1 of Tmean *  ~60 K. This value is typical for locations which tend to fail by COD, as has been discussed in Refs. [12,13]. The local temperature increase induces elevated intra-cavity absorption of laser light and starts a selfamplifying feedback loop of temperature increase up to the material's melting point which is reached on the nanosecond time scale.…”
Section: B Single-pulse Stress-testsmentioning
confidence: 99%
See 1 more Smart Citation